ISLAMIC BANK AND SHARIA BUSINESS UNIT IN INDONESIA: A COMPARISON ON INTELLECTUAL CAPITAL DISCLOSURE PRATICES - Ulum, Ihyaul; Setyawan, Setu; Mohamed, Nafsiah; Amdini, Ismi’ Nor (Universitas Muhammadiyah Malang)
This study aims to compare the intellectual capital disclosures (ICD) in annual reports between Islamic Banks and Sharia Business Unit in 2015. Intellectual capital (ICD) is divided into three main components namely; Human capital, Structural capital and relational capital.Â The components used in this study is the ICD-In framework written by Ulum (2015) which consists of 36 items of intellectual capital. This study uses purposive sampling to determine the sample of Islamic bank and Sharia business units registered in Bank Indonesia in 2015, with a sample of 34 banks. The results indicate that there was a difference practices on intellectual capital disclosures of Islamic banks and Sharia business unit. Islamic banks disclosed on IC higher than Sharia business unit.